Development of a Portable Digital Device Based on a Gas Sensor for Self-Detection of Halitosis - Shafa Marwah Aurilla Kusdinar; Diyah Fatmasari; Supriyana Supriyana (Journal of Community Health Provision, 2026)
Halitosis is a highly prevalent oral health problem that impacts quality of life and social interactions. However, it often goes undetected due to individuals' limited ability to recognize their own breath odor. The limitations of available examination methods, which are often subjective and impractical for self-monitoring, highlight the need for a portable and user-friendly device. This study aimed to develop and evaluate the feasibility of a portable gas sensor-based prototype for self-monitoring oral malodor indicators. The study employed a Research and Development (R&D) approach consisting of needs identification, prototype development, expert validation, and user feasibility testing involving 50 respondents. Content validity was assessed using Aiken’s V, while user acceptance was evaluated descriptively based on the Technology Acceptance Model (TAM). The results showed an Aiken’s V value of 0.916, indicating very high validity in terms of functionality, design, and usability. User feasibility testing demonstrated positive acceptance, with the prototype perceived as useful, practical, and easy to use. These findings indicate that the developed prototype is feasible and acceptable as a self-monitoring tool to support oral health awareness. Further studies are required to evaluate technical performance and clinical validity before wider implementation.